Disaster preparedness amongst pharmacists and pharmacy students: a systematic literature review. (16th August 2020) - McCourt, Elizabeth; Singleton, Judith; Tippett, Vivienne; Nissen, Lisa
Abstract: Objectives: In the aftermath of a disaster, the services provided by pharmacists are essential to ensure the continued health and well-being of the local population. To continue pharmacy services, it is critical that pharmacists are prepared for disasters. A systematic literature review was conducted to explore pharmacists' and pharmacy students' preparedness for disasters and the factors that affect preparedness. Methods: This review was conducted in April 2020 through electronic databases CINAHL, MEDLINE, Embase, PubMed, Scopus and PsycINFO, and two disaster journals. Search terms such as 'pharmacist*', 'disaster*' and 'prepared*' were used. The search yielded an initial 1781 titles. Articles were included if they measured pharmacists or pharmacy students' disaster preparedness. After screening and quality appraisal by two researchers, four articles were included in final analysis and review. Data were extracted using a data collection tool formulated by the researchers. Meta-analysis was not possible; instead, results were compared across key areas including preparedness ratings and factors that influenced preparedness. Key findings: Three articles focused on pharmacy students' preparedness for disasters, and one on registered pharmacists' preparedness. Preparedness across both groups was poor to moderate with <18% of registered pharmacists found to be prepared to respond to a disaster. Factors that potentially influenced preparedness included disaster competency, disaster interventions and demographic factors. Conclusion: For pharmacists, the lack of research around their preparedness speaks volumes about their current involvement and expectations within disaster management. Without a prepared pharmacy workforce and pharmacy involvement in disaster management, critical skill and service gaps in disasters may negatively impact patients.